Kelvin probe force microscopy of the nanoscale electrical surface potential barrier of metal/semiconductor interfaces in ambient atmosphere - Knotek, Petr; Plecháček, Tomáš; Smolík, Jan; Kutálek, Petr; Dvořák, Filip; Vlček, Milan; Navrátil, Jiří; Drašar, Čestmír (Beilstein Journal of Nanotechnology, 2019)
This study deals with the preparation and characterization of metallic nanoinclusions on the surface of semiconducting Bi2Se3 that could be used for an enhancement of the efficiency of thermoelectric materials. We used Au forming a 1D alloy through diffusion (point nanoinclusion) and Mo forming thermodynamically stable layered MoSe2 nanosheets through the reaction with the Bi2Se3. The Schottky barrier formed by the 1D and 2D nanoinclusions was characterized by means of atomic force microscopy (AFM). We used Kelvin probe force microscopy (KPFM) in ambient atmosphere at the nanoscale and compared the results to those of ultraviolet photoelectron spectroscopy (UPS) in UHV at the macroscale. The existence of the Schottky barrier was demonstrated at +120 meV for the Mo layer and −80 meV for the Au layer reflecting the formation of MoSe2 and Au/Bi2Se3 alloy, respectively. The results of both methods (KPFM and UPS) were in good agreement. We revealed that long-time exposure (tens of seconds) to the electrical field leads to deep oxidation and the formation of perturbations greater than 1 µm in height, which hinder the I–V measurements.
Keywords: Kelvin probe atomic force microscope; nanoinclusion; Schottky barrier; thermoelectric materials; work function

CRC Handbook of Thermoelectrics - Slack, G. A. (CRC Press, 1995)

(untitled) - Hicks, L. D.; Dresselhaus, M. S. (Phys. Rev. B, 1993)

(untitled) - Liu, W.; Yan, X.; Chen, G.; Ren, Z. (Nano Energy, 2012)

(untitled) - Li, H.; Tang, X.; Zhang, Q.; Uher, C. (Appl. Phys. Lett., 2009)

(untitled) - Han, M.-K.; Ahn, K.; Kim, H.; Rhyee, J.-S.; Kim, S.-J. (J. Mater. Chem., 2011)

(untitled) - Liu, D.-W.; Li, J.-F.; Chen, C.; Zhang, B.-P. (J. Electron. Mater., 2011)

(untitled) - Faleev, S. V.; Léonard, F. (Phys. Rev. B, 2008)

(untitled) - Zebarjadi, M.; Esfarjani, K.; Shakouri, A.; Bahk, J. H.; Bian, Z. X.; Zeng, G.; Bowers, J.; Lu, H.; Zide, J.; Gossard, A. (Appl. Phys. Lett., 2009)

(untitled) - Narducci, D.; Selezneva, E.; Cerofolini, G.; Frabboni, S.; Ottaviani, G. (J. Solid State Chem., 2012)

(untitled) - Kulbachinskii, V. A.; Kytin, V. G.; Popov, M. Y.; Buga, S. G.; Stepanov, P. B.; Blank, V. D. (J. Solid State Chem., 2012)

(untitled) - Popov, M.; Buga, S.; Vysikaylo, P.; Stepanov, P.; Skok, V.; Medvedev, V.; Tatyanin, E.; Denisov, V.; Kirichenko, A.; Aksenenkov, V.; Blank, V. (Phys. Status Solidi A, 2011)

(untitled) - Park, D.-H.; Kim, M.-Y.; Oh, T.-S. (Curr. Appl. Phys., 2011)

(untitled) - Li, F.; Huang, X.; Sun, Z.; Ding, J.; Jiang, J.; Jiang, W.; Chen, L. (J. Alloys Compd., 2011)

(untitled) - Li, J.-F.; Liu, J. (Phys. Status Solidi A, 2006)

(untitled) - Xiong, Z.; Chen, X.; Huang, X.; Bai, S.; Chen, L. (Acta Mater., 2010)

(untitled) - Dou, Y. C.; Qin, X. Y.; Li, D.; Li, L. L.; Zou, T. H.; Wang, Q. Q. (J. Appl. Phys., 2013)

(untitled) - Zou, T. H.; Qin, X. Y.; Li, D.; Ren, B. J.; Sun, G. L.; Dou, Y. C.; Li, Y. Y.; Li, L. L.; Zhang, J.; Xin, H. X. (J. Appl. Phys., 2014)

(untitled) - Ko, D.-K.; Kang, Y.; Murray, C. B. (Nano Lett., 2011)

(untitled) - Agarwal, K.; Kaushik, V.; Varandani, D.; Dhar, A.; Mehta, B. R. (J. Alloys Compd., 2016)

(untitled) - Agarwal, K.; Mehta, B. R. (J. Appl. Phys., 2014)

(untitled) - Singh, B.; Mehta, B. R.; Varandani, D.; Govind; Narita, A.; Feng, X.; Müllen, K. (J. Appl. Phys., 2013)

(untitled) - Miwa, K.; Salleh, F.; Ikeda, H. (Makara J. Technol., 2013)

(untitled) - Muñoz-Rojo, M.; Caballero-Calero, O.; Martín-González, M. (Appl. Phys. Lett., 2013)

(untitled) - Olaya, D.; Hurtado-Morales, M.; Gómez, D.; Castañeda-Uribe, O. A.; Juang, Z.-Y.; Hernández, Y. (2D Mater., 2017)

(untitled) - Durcan, C. A.; Balsano, R.; LaBella, V. P. (J. Appl. Phys., 2014)

(untitled) - Vanis, J.; Zelinka, J.; Zeipl, R.; Jelinek, M.; Kocourek, T.; Remsa, J.; Navratil, J. (J. Electron. Mater., 2016)

(untitled) - Klimovskikh, I. I.; Sostina, D.; Petukhov, A.; Rybkin, A. G.; Eremeev, S. V.; Chulkov, E. V.; Tereshchenko, O. E.; Kokh, K. A.; Shikin, A. M. (Sci. Rep., 2017)

(untitled) - Yamasaka, S.; Nakamura, Y.; Ueda, T.; Takeuchi, S.; Sakai, A. (Sci. Rep., 2015)

(untitled) - Bala, M.; Gupta, S.; Tripathi, T. S.; Varma, S.; Tripathi, S. K.; Asokan, K.; Avasthi, D. K. (RSC Adv., 2015)

(untitled) - Knotek, P.; Chanova, E.; Rypacek, F. (Mater. Sci. Eng., C, 2013)

(untitled) - Cermak, P.; Ruleova, P.; Holy, V.; Prokleska, J.; Kucek, V.; Palka, K.; Benes, L.; Drasar, C. (J. Solid State Chem., 2018)

(untitled) - Knotek, P.; Tichý, L. (Thin Solid Films, 2009)

(untitled) - Knotek, P.; Tasseva, J.; Petkov, K.; Kincl, M.; Tichy, L. (Thin Solid Films, 2009)

(untitled) - Das, S.; Zazpe, R.; Prikryl, J.; Knotek, P.; Krbal, M.; Sopha, H.; Podzemna, V.; Macak, J. M. (Electrochim. Acta, 2016)

(untitled) - Glatzel, T.; Sadewasser, S.; Lux-Steiner, M. C. (Appl. Surf. Sci., 2003)

(untitled) - Melitz, W.; Shen, J.; Kummel, A. C.; Lee, S. (Surf. Sci. Rep., 2011)

(untitled) - Knotek, P.; Tichy, L.; Kutalek, P. (Thin Solid Films, 2015)

(untitled) - Knotek, P.; Vlcek, M.; Kincl, M.; Tichy, L. (Thin Solid Films, 2012)

(untitled) - Axt, A.; Hermes, I. M.; Bergmann, V. W.; Tausendpfund, N.; Weber, S. A. L. (Beilstein J. Nanotechnol., 2018)

(untitled) - Sadewasser, S.; Nicoara, N.; Solares, S. D. (Beilstein J. Nanotechnol., 2018)

Nanodiamonds - Rezek, B.; Stehlik, S. (Chapter 10 - Surface potential of nanodiamonds investigated by KPFM, 2017)

(untitled) - Watanabe, T.; Fujihira, M. (Ultramicroscopy, 2009)

(untitled) - Zeng, T.-W.; Hsu, F.-C.; Tu, Y.-C.; Lin, T.-H.; Su, W.-F. (Chem. Phys. Lett., 2009)

(untitled) - Yamauchi, T.; Tabuchi, M.; Nakamura, A. (Appl. Phys. Lett., 2004)

(untitled) - Sasahara, A.; Pang, C. L.; Onishi, H. (J. Phys. Chem. B, 2006)

(untitled) - Sasahara, A.; Hiehata, K.; Onishi, H. (Catal. Surv. Asia, 2009)

Handbook of Chemistry and Physics - Lide, D. R. (CRC Press, 2003)

Nanomaterials: Synthesis, Properties and Applications (J. W. Arrowsmith, Ltd., 1996)

(untitled) - Lee, H.; Keun Lee, Y.; Nghia Van, T.; Young Park, J. (Appl. Phys. Lett., 2013)

(untitled) - Tedesco, J. L.; Rowe, J. E.; Nemanich, R. J. (J. Appl. Phys., 2009)

(untitled) - Avouris, P.; Martel, R.; Hertel, T.; Sandstrom, R. (Appl. Phys. A: Mater. Sci. Process., 1998)

(untitled) - Tello, M.; Garcı́a, R. (Appl. Phys. Lett., 2001)

(untitled) - Irmer, B.; Kehrle, M.; Lorenz, H.; Kotthaus, J. P. (Appl. Phys. Lett., 1997)

(untitled) - Fang, T.-H.; Chen, K.-J. (Mater. Trans., 2007)

(untitled) - Shingubara, S.; Murakami, Y.; Morimoto, K.; Takahagi, T. (Surf. Sci., 2003)

(untitled) - Chuang, M.-C.; Chien, H.-M.; Chain, Y.-H.; Chi, G.-C.; Lee, S.-W.; Woon, W. Y. (Carbon, 2013)

(untitled) - Baumgärtel, T.; von Borczyskowski, C.; Graaf, H. (Beilstein J. Nanotechnol., 2013)

(untitled) - Leontie, L.; Caraman, M.; Alexe, M.; Harnagea, C. (Surf. Sci., 2002)

(untitled) - Zhong, G.; Wang, Y.; Dai, Z.; Wang, J.; Zeng, Z. (Phys. Status Solidi B, 2009)

(untitled) - Torruella, P.; Coll, C.; Martín, G.; López-Conesa, L.; Vila, M.; Díaz-Guerra, C.; Varela, M.; Ruiz-González, M. L.; Piqueras, J.; Peiró, F.; Estradé, S. (J. Phys. Chem. C, 2017)

(untitled) - Lyutakov, O.; Huttel, I.; Siegel, J.; Švorčík, V. (Appl. Phys. Lett., 2009)

(untitled) - Irfan, I.; James Turinske, A.; Bao, Z.; Gao, Y. (Appl. Phys. Lett., 2012)

Novel Materials Development for Polycrystalline Thin-Film Solar Cells: Final Subcontract Report, 26 July 2004--15 June 2008 - Keszler, D. A.; Wager, J. F. (Office of Scientific and Technical Information (OSTI), 2008)

(untitled) - Balakrishnan, M.; Kozicki, M. N.; Poweleit, C. D.; Bhagat, S.; Alford, T. L.; Mitkova, M. (J. Non-Cryst. Solids, 2007)

(untitled) - Adam, J.-L.; Zhang, X. (Elsevier, 2014)